2004
DOI: 10.1590/s0103-64402004000300002
|View full text |Cite
|
Sign up to set email alerts
|

Lack of repair of rat skull critical size defect treated with bovine morphometric protein bound to microgranular bioabsorbable hydroxyapatite

Abstract: The ability of a pool of bovine bone morphogenetic proteins bound to synthetic microgranular hydroxyapatite (BMPb-HA) to stimulate bone repair was determined in rat critical size defects. An 8-mm diameter defect was created in the calvaria of 25 rats. In 15 rats, the defects were filled with BMPb-HA homogenized with blood (experimental group), and in 10 rats the defects were filled only with blood clots (control). The calvariae of experimental rats were collected 1, 3 and 6 months after surgery and of the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
(12 reference statements)
2
14
2
2
Order By: Relevance
“…A prominent foreign body reaction was observed around HA agglomerates, more so in Group B. Brandão et al 22 evaluating the same hydroxyapatite, mixed or not with pBMPs implanted in rat alveolar wounds, achieved delay in wound healing in both groups, suggesting an absence of osteogenic properties in these materials. A similar finding was observed by Ferreira et al 23 while using the same hydroxyapatite bound to pBMPs for treatment of critical size calvarial defects in rats. The authors showed occurrence of intense foreign body reaction around agglomerates of BMP-HA particles with high number of macrophages and multinucleate giant cells.…”
Section: Discussionsupporting
confidence: 86%
“…A prominent foreign body reaction was observed around HA agglomerates, more so in Group B. Brandão et al 22 evaluating the same hydroxyapatite, mixed or not with pBMPs implanted in rat alveolar wounds, achieved delay in wound healing in both groups, suggesting an absence of osteogenic properties in these materials. A similar finding was observed by Ferreira et al 23 while using the same hydroxyapatite bound to pBMPs for treatment of critical size calvarial defects in rats. The authors showed occurrence of intense foreign body reaction around agglomerates of BMP-HA particles with high number of macrophages and multinucleate giant cells.…”
Section: Discussionsupporting
confidence: 86%
“…Critical defects do not regenerate during the life span of the animal [12,26,[34][35][36]; thus they are a good model for the evaluation of the osteogenic potential of biomaterials designed to be used in bone regeneration. In our work we used 8 mm for the diameter of the defect in the calvaria of rat.…”
Section: Discussionmentioning
confidence: 99%
“…It was the Nuremberg Code (1947) that determined that research on humans must be based on the results of animal experimentation -a position reinforced by the Helsinki Declaration in 1975 14 . As equipment, procedures and drugs were developed, scientific investigation was performed in vitro, preferably in a standardized manner (International Organization for Standardization -ISO 10993-6, 1992) 15 , and in animals of small (rats, mice and guinea pigs) 1,3,6 , medium (rabbits, mini pigs, cats and dogs) 4,2,7,9 and large size (sheep and pigs) 5,8,16 . The choice of the model for an experiment is determined by factors such as cost, technical viability of the procedure, scientific principles, available data base and appropriateness of the model vis-à-vis the project 12 .…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The use of animals in biomedical research has been recommended for perfecting and validating existing procedures 1,2,3 , developing new materials 4,5,6 and understanding the various physiological and pathological processes 7,8,9 because there are no in vitro models capable of fully mimicking the complexity of the human organism.…”
Section: Introductionmentioning
confidence: 99%